Head Nurse Leadership and Blame Culture Among Nurses: A Cross-Sectional Study in a Public Hospital - Giovanni Iga Firmanda; Rita Dewi Sunarno; Wahyu Nur Pratiwi; Aries Wahyuningsih; Moch Gandung Satriya (STIKES Adi Husada, 2026)
Head nurse leadership plays an important role in shaping organizational culture and influencing nurses’ perceptions of psychological safety in hospital settings. Ineffective leadership may contribute to fear-based work environments, reduced psychological safety, and the emergence of a blame culture among nurses, which can hinder open communication and learning from clinical errors. This study aimed to examine the relationship between head nurse leadership and blame culture among nurses in a public hospital. A quantitative analytic study with a cross-sectional design was conducted involving 220 nurses recruited from inpatient, intensive care, emergency, and outpatient units of a public hospital. Data were collected using structured questionnaires measuring perceived overall head nurse leadership and blame culture in clinical practice. Data were analyzed using descriptive statistics and Pearson correlation analysis using SPSS version 26. The results showed that overall head nurse leadership was perceived at a moderately high level (3.62 ± 0.54), while blame culture was categorized as moderate (3.41 ± 0.63). Pearson correlation analysis demonstrated a significant moderate negative relationship between head nurse leadership and blame culture (r = -0.528, p = 0.001), indicating that higher perceived leadership was associated with lower levels of blame culture among nurses. These findings highlight the importance of strengthening effective and supportive leadership practices among head nurses to promote a psychologically safe and learning-oriented organizational culture in hospital settings.